Nineteenth-century religion, literature and society.
1 online resource (xiv, 425 pages)
Keywords: Part of a four-volume set, this fourth volume on 'Disbelief and New Beliefs' explores the transformation of the religious landscape of Britain and its imperial territories during the nineteenth century as a result of key cultural and intellectual forces. The complete four-volume historical resource provides new opportunities for investigating the relationship between religion, literature and society in Britain and its imperial territories by making accessible a diverse selection of harder-to-find primary sources. These include religious fiction, poetry, essays, memoirs, sermons, travel writing, religious ephemera, unpublished notebooks and pamphlet literature. Spanning the long nineteenth century (c.1789-1914), the resource departs from older models of 'the Victorian crisis of faith' in order to open up new ways of conceptualising religion.